Total and speciation analyses of heavy metals in the sand fraction of Nigerian oil sands for human and ecological risk assessment. Issue 8 (17th November 2017) - Oyewole, F. G.; Adebiyi, F. M.
ABSTRACT: Total metal analysis and metal speciation of sand fraction of Nigerian oil sands were done to extract and partition heavy metals into six operationally defined fractions in order to assess environmental and health implications of the oil sand development. Soxhlet extraction of bitumen from the oil sand was done using toluene. Traces of water and extracting solvent were removed at 70°C from the sand fraction using oven. Elemental analysis was performed by Atomic Absorption Spectrophotometry. The heavy metals except Cu have low Pollution index values. Negative geo-accumulation index was obtained for the metals except Cu, indicating that the oil sands were uncontaminated with the metals. Strong and significant positive correlations existed between Fe/Pb, Zn/Cu, Cd/Pb, Ni/Cd, Ni/Pb, Cd/Fe, Ni/Fe and Cr/Zn, while strong and significant negative correlations existed between Mn/Pb and As/Mn, indicating common sources or chemical similarities and vice versa. T -test results indicated significant differences between the concentrations of the metals. Cross-plot analysis showed strong positive correlation between the sand fraction and Nigerian bitumen. Speciation analysis indicated highest and lowest indices of metal mobility for Zn and Pb, respectively. This study concluded that the sand fraction may not pose any environmental risks from elemental point of view.